Improving Colloidal Learning Outcomes through Problem Based Learning in 11th Vocational School Students - Helen Soraya Sirait; Hartono Hartono; Eddy Dharmansyah (Research in Education, Technology, and Multiculture, 2022)
Abstract: This Classroom Action research aims to know whether Problem Based Learning can improve students' chemistry learning outcomes in class XI SMK Negeri 4 Palembang. This Research use Subject at students of class XI TITL 3 SMK Negeri 4 Palembang, amount to 38 students. This research which is implemented in two cycles. Data obtained from each cycle were analyzed to determine the development of learning and as a reflection thing in the next cycle. Data collection is done through an evaluation test at the end  of each learning cycle. The collected data was analyzed statistically using student learning outcomes average and percent student's classical. In the first cycle the average score of students is 61 and the percentage of students' classical is 44,74%. While in the second cycle there is an increase in student learning that can be seen from the average score of students by 83 and percent classical student to 86.84%. Therefore, the application of Problem Based Learning model in colloid chemistry subject can improve student learning outcomes. Keywords: problem based learning, chemistry learning outcomes, classroom action research.